Population biology of Uca thayeri Rathbun, 1900 (Brachyura, Ocypodidae) in a subtropical South American mangrove area: Results from transect and catch-per-unit-effort techniques - Costa, T. M.; Negreiros-Fransozo, M. L. (Brill Academic Publishers, 2002)
The population biology of Uca thayeri was studied in a subtropical mangrove in Ubatuba, State of São Paulo, Brazil. Two sampling techniques were used: transect sampling and catch-per-unit-effort. Size frequency distribution, sex-ratio, and reproductive period were analysed. For juvenile crabs (CW < 4.6 mm), the transect procedure was most efficient, while ovigerous females were most collected during the capture effort. Males were most numerous in the transect technique, while in the catch-per-unit-effort there was no difference between sexes. The species showed a different size frequency distribution for each sampling procedure. The reproduction of U. thayeri is seasonal, being more pronounced in the warmer months of the year. However, juveniles occurred all over the year, although more numerous in the colder months. The success of the species in reproductive activity and the constant colonization of the area can be attributed to the availability of food resources and differential occupation of the habitat by ovigerous females.